Do Some Dynamic Risk Factors Signal Imminent Recidivism? Testing the Conceptual Distinction Between Stable and Acute Dynamic Risk Factors - Davies, Simon T. (Criminal justice and behavior, 2023)
In correctional practice, acute and stable dynamic risk factors are conceptually distinct. This distinction, however, has limited empirical support. We suggest that when compared with stable factors, change in acute risk factors over short time periods should demonstrate a stronger association with imminent recidivism. Using a sample of high-risk New Zealand male parolees, we examined recidivism and change in scores on the Acute and Stable subscales from the Dynamic Risk Assessment for Offender Re-entry (DRAOR). Short-term acute change was more strongly associated with imminent recidivism than short-term stable change. Notably, Acute change predicted imminent recidivism even after controlling for the most current acute assessment. Furthermore, variability across Acute, but not Stable, subscale scores enhanced prediction of imminent recidivism. These findings support the largely untested theoretical distinction between stable and acute risk factors, and tentatively support using DRAOR’s Acute subscale to guide immediate intervention decisions.